Spontaneous Spinal Epidural Hematoma During Simultaneous Tocilizumab and Warfarin Use in a Patient With Rheumatoid Arthritis: Is There a Drug Interaction Between Tocilizumab and Oral Anticoagulants? - Seçilay GÜNEŞ,; Haydar GÖK,; Şebnem ATAMAN,; Şehim KUTLAY, (Archives of Rheumatology, 2020)
Interleukin 6 (IL-6) plays a main role in the immunopathogenesis of rheumatoid arthritis (RA). Tocilizumab (TCZ) is a humanized immunoglobulin G1 monoclonal antibody against the human IL-6. Warfarin sodium is an oral anticoagulant that is primarily metabolized by cytochrome P450 2C9 (CYP2C9). Impaired metabolism of this low therapeutic index drug is important as it may result in serious bleeding. In this article, we present a 56-year-old female patient with RA, treated with TCZ and warfarin sodium and presented spontaneous spinal epidural hematoma (SSEH) of thoracic spine although international normalized ratio levels were in normal ranges. One week after decompressive surgery for hematoma, a cervical spine abscess developed which resulted in her death. To the best of our knowledge, this is the first case of RA developing SSEH while taking TCZ and warfarin sodium together. Although it is difficult to attribute the severe bleeding to TCZ treatment, clinicians should be aware that concomitant use of oral anticoagulants and TCZ might result in potentially fatal complications in patients with RA.